Analysis of heavy metals (cadmium, chromium, lead, manganese, and zinc) in well water in East Java Province, Indonesia - Sholehhudin, Mochammad; Ramli, Azizah; Sumantri, Arif; Mohd Sham, Shaharuddin; Zakaria, Zainul Amiruddin; Latif, Mohd Talib (Universiti Putra Malaysia, 2021)
Introduction: Indonesia is one of the countries whose inhabitants use well water for drinking and cooking purposes. In East Java, 48.90% of the population uses well water for their daily needs. Well water contained heavy metals had bad effects on health such as cancer, damage of liver, kidneys, and others. The objective of this study was to evaluate the concentration of heavy metals in well water and relate them to a potential health outcomes. Methods: The method used in this study was analytical descriptive. Data used was secondary from East Java Environmental Office. A total of 101 samples were collected from 33 locations. There were 5 heavy metals analyzed, namely cadmium, chromium, lead, manganese, and zinc. Equipment using ICPMS and AAS. Data analyzed with descriptive statistics by SPSS. Data obtained were compared to the WHO Standard for Drinking Water Quality. Results: Concentration for cadmium was 0.002 mg/l, followed by manganese at 1.80 mg/l and zinc at 0.020 mg/l. Besides, all water samples had levels of chromium and lead below the detection limit. Conclusion: All heavy metals had concentrations below the maximum allowable standard, except for five water samples from three locations with levels of manganese which was above the maximum standard. Long term effects of manganese include neurological problems, intelligence, and low birth weight. Further studies need to be done to determine the source of manganese contamination. It is recommended that bottled water is used for drinking purposes in an area where heavy metal concentration is above the allowable limit.